Osteopenic syndrome and chronic obstructive pulmonary disease among residents of lowland of the Kyrgyz Republic taking into account risk factors - A. A. Asanbaeva; O. V. Lobanchenko; N. N. Brimkulov (Научно-практическая ревматология, 2024)
The aim of the study was to identify the relationship between bone mineral density disorders and chronic obstructive pulmonary disease among residents of Bishkek, Kyrgyz Republic, taking into account risk factors.Material and methods. 200 residents of lowland (mean age 56,9±1,7 years) were examined. Bone mineral density (BMD) was determined by dual-energy X-ray absorptiometry.Results. Chronic obstructive pulmonary disease (COPD) was almost 2-fold more common among patients with low BMD than healthy controls (63.0% and 34.8% of cases, respectively; p<0.001), despite the same frequency of smoking. Other independent predictors of low BMD were glucocorticoid intake and age.Conclusion. The occurence of COPD is an independent risk factor for the development of osteopenia/osteoporosis even after age and other known risk factors adjustment in lowland residents of the Kyrgyz Republic.